2019
DOI: 10.1073/pnas.1900251116
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracing and targeting of IL17RB + tuft cell-like human colorectal cancer stem cells

Abstract: Cancer stem cell (CSC)-specific markers may be potential therapeutic targets. We previously identified that Dclk1, a tuft cell marker, marks tumor stem cells (TSCs) in mouse intestinal adenomas. Based on the analysis of mouse Dclk1 + tumor cells, we aimed to identify a CSC-specific cell surface marker in human colorectal cancers (hCRCs) and validate the therapeutic effect of targeting it. IL17RB was distinctively expressed by Dclk1 + mouse intestinal tumor cells. Using Il17rb-CreERT2-IRES-EGFP mice, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 44 publications
(73 reference statements)
3
49
0
3
Order By: Relevance
“…Furthermore, Goto et al (2019) found IL17RB, a tuft cell marker, is distinctively expressed by DCLK1 + mouse intestinal tumor cells and regulates the function of tuft cell-derived cancer stem cell. The expression of IL17RB was then proven to be a potential marker for the lineage tracing of human colorectal cancer stem cells ( Goto et al, 2019 ). However, in human pancreas, DCLK1, a tuft cell marker in rodents, failed to co-localize with ChAT + cholinergic tuft cells ( Schütz et al, 2019 ).…”
Section: Pathophysiological Roles Of Ach Produced By Tuft Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Goto et al (2019) found IL17RB, a tuft cell marker, is distinctively expressed by DCLK1 + mouse intestinal tumor cells and regulates the function of tuft cell-derived cancer stem cell. The expression of IL17RB was then proven to be a potential marker for the lineage tracing of human colorectal cancer stem cells ( Goto et al, 2019 ). However, in human pancreas, DCLK1, a tuft cell marker in rodents, failed to co-localize with ChAT + cholinergic tuft cells ( Schütz et al, 2019 ).…”
Section: Pathophysiological Roles Of Ach Produced By Tuft Cellsmentioning
confidence: 95%
“…With increasing evidence highlighting the role of ACh as an autocrine and paracrine hormone, cholinergic targets have drawn widespread attention in pulmonary diseases ( Meurs et al, 2013 ; Voisin et al, 2017 ), Hirschsprung’s disease ( O’Donnell et al, 2020 ) and cancers ( Westphalen et al, 2014 ; Schütz et al, 2015 ; Pozo et al, 2018 ; Friedman et al, 2019 ; Goto et al, 2019 ). Tuft cells, considered as a crucial non-neuronal ACh source, have also been discussed in several disease models.…”
Section: Potential Clinical Applicationmentioning
confidence: 99%
“…In addition, in vitro co-culture experiments showed that nerves fail to support organoid growth in the absence of Dclk1+ tuft cells, suggesting that Dclk1+ cells are involved in the integration of neuronal signals in the epithelium [76]. More recently, Goto et al identified interleukin 17 receptor B (IL17RB) as a cell-specific marker of tuft cells, and showed that IL17RB regulates tuft cell-derived cancer stem cell function and could be a therapeutic target [77].…”
Section: Ach Signaling and Colon Cancermentioning
confidence: 99%
“…However, traditional transplantation assays often disrupt the native microenvironment of TICs and led to alteration of TIC characteristics [ 16 ]. To avoid the shortcomings of these assays, lineage tracing of genetically labeled cells has been used to identify TICs in vivo [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%